Evaluation of phenological development and agronomic traits in exotic common bean germplasm across multiple environments - Basavaraja, T.; Tripathi, Anupam; Chandora, Rahul; Pratap, Aditya; Manjuanatha, L.; Gurumurthy, S.; Singh, Mohar; Rana, Jai Chand; Kumar, S. D. Nitesh; Katiyar, P. K.; Singh, Bansa (Cambridge University Press, 2023)
Twenty-nine exotic common bean germplasms and three elite cultivars were examined for phenotypic diversity in two bean-producing environments (Kanpur and Shimla) across three winter seasons and one rainy season. The estimate of genetic variability parameters revealed that the exotic bean germplasm has enough diversity for all the evaluated features. The highest genotypic and phenotypic coefficients of variation were found in seed yield, followed by 100-seed weight, pods per plant and pod length. Furthermore, seed yield was the most heritable and genetically advanced quantitative feature, followed by 100-seed weight, pod length and pods per plant. According to a trait association study, the days to maturity of phenological traits have a strong positive correlation with the days to initial flowering and the days to 50% flowering. Pods per plant and seeds per pod most strongly influence increased grain yield. The first two principal components accounted for 63.3% of the variation and demonstrated significant diversity among exotic bean lines for the traits studied, according to the principal component analysis. According to the hierarchical clustering analysis, 29 accessions and three cultivars were divided into three groups. Cluster I contains early flowering and maturing accessions, while cluster III contains high pods per plant and an increased grain yield of germplasms. The fundamental source of phenological fluctuations in both environmental circumstances is temperature. This study found four genetically divergent and stable performance accessions, including EC932021, EC932189 (earliness), and EC931452, EC931971 (high grain yield), which may aid in the establishment of a bean breeding programme.